Studying the Effects of Listening to Quran on Human Mood - Shaikh, Zeeshan K (2009)
Many Muslims believe that listening to their holy book Quran, has an effect on their state of mind or mood. Each Surah of Quran emphasizes on a unique topic, warns of wrong doings and provides the correct way of handling a particular situation. A person waiting for a job interview or promotion who often becomes frustrated can listen or read Surahs that may help him feel better. There has been no work done that attempted to study the e ects of Quran on the mood of people. Furthermore, when people are in a tough situation or in a bad mood,they seldom think about listening or reading Quran. In these situations if there is a device with them that can detect their mood and suggest a particular surah, it can help them feel better. This dissertation presents a proof-of-concept mobile application that can run on any Java enabled phone, which takes user's feedback on Surahs, stores the feedback for further analysis and provides a simple suggestion mechanism.